Prompt acceleration of magnetospheric electrons to ultrarelativistic energies by the 17 March 2015 interplanetary shock. Issue 8 (15th August 2016) - Kanekal, S. G.; Baker, D. N.; Fennell, J. F.; Jones, A.; Schiller, Q.; Richardson, I. G.; Li, X.; Turner, D. L.; Califf, S.; Claudepierre, S. G.; Wilson, L. B.; Jaynes, A.; et al.
Abstract: Trapped electrons in Earth's outer Van Allen radiation belt are influenced profoundly by solar phenomena such as high‐speed solar wind streams, coronal mass ejections (CME), and interplanetary (IP) shocks. In particular, strong IP shocks compress the magnetosphere suddenly and result in rapid energization of electrons within minutes. It is believed that the electric fields induced by the rapid change in the geomagnetic field are responsible for the energization. During the latter part of March 2015, a CME impact led to the most powerful geomagnetic storm (minimum Dst  = −223 nT at 17 March, 23 UT) observed not only during the Van Allen Probe era but also the entire preceding decade. Magnetospheric response in the outer radiation belt eventually resulted in elevated levels of energized electrons. The CME itself was preceded by a strong IP shock whose immediate effects vis‐a‐vis electron energization were observed by sensors on board the Van Allen Probes. The comprehensive and high‐quality data from the Van Allen Probes enable the determination of the location of the electron injection, timescales, and spectral aspects of the energized electrons. The observations clearly show that ultrarelativistic electrons with energies E  > 6 MeV were injected deep into the magnetosphere at L  ≈ 3 within about 2 min of the shock impact. However, electrons in the energy range of ≈250 keV to ≈900 keV showed no immediate response to the IP shock. Electric and magnetic fields resulting from the shock‐driven compression complete the comprehensive set of observations that provide a full description of the near‐instantaneous electron energization. Key Points: March 2015 IP shock event resulted in near‐instantaneous energization of electron to ultrarelativistic energies Electrons energization was mostly pitch angle independent Injected‐electron spectra were harder than preinjection spectra at all pitch angles